Entomological survey of vector of chikungunya disease in chikungunya affected areas of Surat Thani - ทองขาว, คณพศ; ฤทธาธร, วิโรจน์; ยศเมฆ, สุพิทย์ (Disease Control Journal, 2015)
The objectives of this study were to investigate the species and density of the chikungunya disease vector in the chikungunya affected areas and to find the relationship of the vector density against temperature, relative humidity and rainfall. The entomological survey of vectors was conducted in-house, outside-house and in the garden at Moo 5, ThamPuong village, Phanom district, Surat Thani province during February, April, June and August 2011. The results showed that Ae. aegypti in-house was not found. Where as Ae. albopictus at all study sites was found through out the year with high density. The highest density of Ae. albopictus was in June. The biting rates at in-house, outside-house, and the garden were 0.104, 4.250 and 11.396 individuals per man per hour, respectively. The vector densities of Ae. albopictus at in-house, outside-house and the garden were high significantly different (p<0.001). Ae. albopictus is was considered as a primary vector of chikungunya disease in Surat Thani province. The relationship of the Ae. albopictus density against temperature, humidity and rainfall were correlated. The results showed that rainfall and temperature were not correlated with the density of Ae. albopictus. The relative humidity in February, June and August were not correlated with the density of Ae. albopictus. Except in April, there lative humidity was corresponded to the density of Ae. albopictus statistically significant (r = 0.249, p = 0.035). Therefore the entomological surveillance should be initiated due to the emerging vector borne diseases will be always spread in the future.